PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN METODE DRILL BERBANTUAN MEDIA GAMBAR SERI DI SD - Krantika, Krantika; Sugiyono, Sugiyono; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is that students have difficulty writing essays and telling the essay in their own language well, clearly, and less creatively in developing sentences. The method used in this research is descriptive method with the form of classroom action research and is collaborative. The place of the study took place in the 14th Elementary School of Peresak, with the subject of research of teachers and class III students totaling 26 people. Data collection techniques used were direct observation techniques and document scrutiny with data collection tools namely IPKG 1 sheet, IPKG 2 sheet, and document student learning outcomes.The research took place in 3 cycles with one meeting in each cycle. Assessment of learning planning results from cycles I, II, and III, namely 2.57, 3.37, and 3.52. Assessment of the results of the implementation of learning from cycles I, II, and III are 2.69, 3.22, and 3.58. Description essay writing skills using drill methods in cycles I, II, and III are 65.86, 79.50, and 84.61. Thus, research using the Assisted Drawing Series Drill Media Method in Class III of Public Elementary School 14 Bengkayang Presenter has increased in each cycle.Â Keywords:Learning Outcomes, Drill Method, Class III students